# Simplifying Algebraic Expressions

• May 5th 2009, 10:17 PM
jedimaster700
Simplifying Algebraic Expressions
How would i simplify this expression by expanding the brackets and collecting the like terms?

5h(7-d) + 11hd

• May 5th 2009, 11:02 PM
Hello jedimaster700
Quote:

Originally Posted by jedimaster700
How would i simplify this expression by expanding the brackets and collecting the like terms?

5h(7-d) + 11hd

Welcome to Math Help Forum!

$\displaystyle 5h(7-d) = 5h\times 7 - 5h\times d=35h-5hd$

So $\displaystyle 5h(7-d) + 11hd=35h - 5 hd +11hd =35h +6hd$

If you like, you can now factorise the final answer, and write $\displaystyle 35h+6hd=h(35+6d)$

OK?

• May 6th 2009, 01:35 AM
jedimaster700
Hm, yes it made sense until you came to...

35h - 5hd + 11hd = 35h + 6hd

Wouldn't 35h - 5hd = 30d?

Then 30d + 11hd = 41hd?
• May 6th 2009, 09:28 AM
Like terms
Hello jedimaster700
Quote:

Originally Posted by jedimaster700
Hm, yes it made sense until you came to...

35h - 5hd + 11hd = 35h + 6hd

Wouldn't 35h - 5hd = 30d?

Then 30d + 11hd = 41hd?

In your first post, you said that the question talked about collecting 'like terms'. You obviously aren't sure what this means. $\displaystyle 35h$ and $\displaystyle 5hd$ are not like terms, so you can't simplify them in the way you're trying to do here.

You need to find out what 'like terms' means. Here's a web-site that might help: BBC - GCSE Bitesize - Re-arranging symbols

Best of luck!